The Efficacy of Process-Tracing Technologies for Supporting Academic Writing Instruction: A Lesson Learned from Vietnam - Wang, Huang Yen; Dolba, Sammy Q.; Zamorano, Alex (Journal of Language and Literature Studies, 2023)
Writing-process research has undergone a transformative shift from relying on methods that were impractical for classroom settings, such as direct or video-based observations and concurrent verbal reports, to adopting less-obtrusive techniques like keystroke logging and eye tracking. The latter methods have become increasingly feasible due to the resolution of software and cost-related concerns, making them more accessible for pedagogical applications. Therefore, this study aims to investigate the efficacy of process-tracing technology for supporting academic writing instruction at a middle school in Vietnam. To carry out the research process, the researchers applied qualitative study. The participants in this study comprise a group of learners attending a middle school in Vietnam. Their involvement in the research revolves around the meticulous tracing of their writing process as they engage in the production of argumentative texts, with a particular focus on the utilization of technology during this endeavor. Data collection involved the application of both interviews and observations to gather comprehensive insights into the phenomenon under investigation. The findings of the study showed that process-tracing technology is able to help teachers and learners to control their academic writing achievement. The conclusion showed that the integration of process-tracing technology, combining keystroke logging and eye tracking, has proven to be a highly effective and valuable tool for supporting academic writing.